An Integrative Approach to Early Childhood Education: Learning from Nature and Religion Values - Kartika, Dwi Indah (JURNAL PENELITIAN, 2025)
Early childhood education is critical for building a strong foundation for children’s holistic development. Exploring the integration of nature-based and religion-based learning in Desa Petengan, Bandung, Indonesia by using the case of Yayasan Al Anbiya wal Mursalin, it addresses two questions: (1) how is the combination between learning from nature and religious values applied in early childhood education? (2) why is it important to integrate nature-based and religious-based learning early education setting? The study examines the implementation of nature-religion integrated learning in early childhood education, and its significance for children’s holistic development. A descriptive-explorative qualitative design is employed with data collected through classroom observations, interviews and documentation analysis. Findings reveal that integration of nature and religion not only enriches learning experiences but also fosters cognitive, socio-emotional, moral, and ecological awareness among children. These findings indicate that contextual learning grounded in local wisdom and spiritual values strengthens the sustainability of early childhood in rural communities. The study provides valuable implications for policy makers, educators, and researchers seeking to promote sustainable and value-based early education. Combination between learning from nature and religious values in early childhood education shows two learning domains, they are environmental (nature) and spiritual (religious). The combination is directly examined the process and practice of integration. Moreover, it answers and explores community response and impact by understanding why the model gains social legitimacy. It connects the outcome of integration (trust, satisfaction) with the value-based learning model. Model of pedagogical implementation and social validation combine natural and religious learning there.